Geometric matching for free-form 3D object recognition - Hügli, Heinz; Schütz, Christian; Semitekos, Dimitrios (My University, 1995)
This paper investigates a new approach to the recognition of 3D objects of arbitrary shape. The proposed solution follows the principle of model-based recognition using geometric 3D models and geometric matching. It is an alternative to the classical segmentation and primitive extraction approach and provides a perspective to escape the difficulties found with it when dealing with free-form shapes. The heart of this new approach is geometric registration which is performed by a closest point matching algorithm. Reported investigations examine the practical effectiveness of this approach for views obtained from range imaging and address relevant aspects of associated computational costs. The paper proposes solutions allowing to keep track with these costs and presents results assessing the practical feasibility of this approach.
Keywords: free-form 3D object recognition; pose estimation; range imaging; closest point matching